Does mental health limit organizational behavior, or not? A study drawn on resource conservation - Singh, Aarthi Chandrasantha; Bhuvaneswari, Mohanraj (Frontiers in Psychology, 2023)
The current study is rooted in the theory of conservation of resources, exploring the associations between mental health factors namely stress, anxiety and depression with organizational citizenship behavior and counterproductive wok behavior. Data gathered from an Indian automobile sector revealed interconnections between the variables. It was found that stress, anxiety and depression have a positive relationship with OCB and stress and anxiety have negative relationship with CWB. The manuscript further evaluates the results drawing upon conservation of resources theory as we find striking differences between our hypotheses and results, and that opens up new avenues for future research.